Effect of Teachers’ Perception Towards Performance Appraisal on Its Implementation in Public Secondary Schools in Mbooni East Sub-County, Kenya - Waema, Mumo; Munguti, Stephen; Nzioki, Susan (EdinBurg Peer Reviewed Journals and Books Publishers, 2024)
The purpose of this study was to investigate the effect of teachers’ perception of performance appraisal on its implementation in public secondary schools in Mbooni East Sub-County, Kenya. The study was based on the Expectancy Theory of Motivation and was conducted using a descriptive survey design. The target population was 47 Principals and 416 teachers in public secondary schools in Mbooni-East Sub-County. A sample of 19 Principals and 126 teachers was selected through both stratified and simple random sampling. Quantitative data was then analyzed using descriptive statistics. Qualitative data was categorized into themes in accordance with the research objective and presented in narrative form. Results revealed that teachers’ perception of performance appraisal affected its implementation. In as much the teachers’ both negative and positive perceptions about the implementation of performance appraisal, they noted that performance appraisal had had a positive impact on their teaching standards and their teaching profession as a whole. The Ministry of Education should organize more workshops and seminars to sensitize teachers on the importance of performance appraisal and how to use the TPAD tool. The Ministry should also engage teachers in public participation to ensure that they incorporate the required changes in the performance appraisal process to make it more productive.
Keywords: Teachers’ Perception, Performance Appraisal, Implementation